Efficiency and Complication of 577-nm Laser Membranotomy for the Treatment of Retinal Sub-Inner Limiting Membrane Hemorrhage - Zhang, Yongpeng; Li, Jipeng; Cao, Xusheng; Zhou, Haiying; Jia, Liyun; Gao, Liqin; Li, Zhihua; Zhang, Xifang; She, Haicheng; Ma, Kai; Peng, Xiaoyan (Frontiers in Ophthalmology, 2022)
Objective: We investigate the clinical efficiency and complication for treatment of retinal sub-inner limiting membrane (sub-ILM) hemorrhage by 577nm laser membranotomy. Methods: The clinical features, ocular fundus photography and SD-OCT image of patients who received 577nm laser membranotomy for sub-ILM hemorrhage were assessed from January 2017 to April 2022 in this retrospective cases series study. Results: Total of 19patients (19 eyes) were treated for sub-ILM hemorrhage of the macula, in which 8 were female and 11 were male. The age was from 15 to 83 years old (with average age 49.05±19.41 years old). Right eye was affected in 12 patients and left eye in 7 patients. The following-time after laser was from 0.5 month to 9 months (with average following-time of 3.25±2.45 months). One patient was failure in 577nm laser membranotomy and 18 patients were successful with the success rate 94.74%. The best corrected visual acuity (BCVA) before laser was from figure count to 40/200 and the BCVA after laser was from 20/2000 to 20/20. The complications after laser included macular hole (1 patient), macular epi-membrane (1 patient), vitreous hemorrhage without absorption (2 patients) and sub-ILM cavity (12 patients). Conclusions: 577nm laser is effective in treating of sub-ILM hemorrhage with high successful rate. The complication after laser should be paid attention to and vitrectomy was needed with long-lasting vitreous hemorrhage and macular hole.